Vinyl chloride-based copolymer microspheres and method for producing the same, resin composition and resin product and method for producing the same
Patent Information
- Application Number
- CN202610787532.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-02
- Publication Date
- 2026-10-20
AI Technical Summary
[0003]辐射固化工艺是工业上用于PVC交联的一种,利用紫外线(UV)或电子束(EB)等高能辐射引发PVC材料中的光引发剂或辐射敏感剂,使其发生交联或聚合反应,虽然不依赖大量的热量,但是辐射源实际输出量不确定,引发剂和敏感剂参与反应的量不确定,固化交联程度不可控,且成本较高
[0033]本发明中,在氯乙烯系共聚物微球中使用交联氯乙烯系微球作为核部并且在核部接枝有包括基于具有双键和烷氧基的硅烷的单元和基于(甲基)丙烯酸酯的单元的接枝部。因此,在该氯乙烯系共聚物微球作为氯乙烯系树脂制品的填充材料时,不仅组成上与氯乙烯系树脂的亲和性优异,而且还具有作为大分子交联剂通过硅烷键的水解缩合形成交联网络的潜力。因此,本发明的氯乙烯系共聚物微球显示出与氯乙烯系树脂的亲和性高、并且可以以高水平地改善树脂制品的力学性能、且能够抑制树脂制品的透明性的下降。
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to a vinyl chloride copolymer microsphere and its manufacturing method, a resin composition and resin product and their manufacturing method. Background Technology
[0002] Polyvinyl chloride (PVC) is a widely used thermoplastic, second only to polyolefins in global production. Due to its excellent physical properties, good acid and alkali resistance, and low cost, it is widely used in window frames, flooring, packaging, and medical tubing. The presence of C-Cl bonds in rigid PVC leads to strong polar interactions between polymer chains, resulting in high rigidity and brittleness, which hinders its practical application in high-performance structural materials. To overcome these drawbacks, current industrial practices primarily involve crosslinking or blending fillers or other rigid resins into PVC to enhance its mechanical properties.
[0003] Radiation curing is an industrial process used for PVC crosslinking. It utilizes high-energy radiation such as ultraviolet (UV) or electron beam (EB) to initiate photoinitiators or radiation-sensitive agents in PVC materials, causing them to undergo crosslinking or polymerization reactions. Although it does not rely on a large amount of heat, the actual output of the radiation source is uncertain, the amount of initiator and sensitive agent participating in the reaction is uncertain, the degree of curing and crosslinking is uncontrollable, and the cost is relatively high.
[0004] Furthermore, in traditional blending methods, the affinity between inorganic or organic fillers or other rigid resins and PVC is insufficient, which impairs the improvement of mechanical properties. Additionally, the transparency of resin products obtained through blending methods sometimes decreases.
[0005] In addition, the inventors’ previous work provided an alkoxysilane-functionalized crosslinked polyvinyl chloride microsphere and its preparation method (Chinese patent application CN202511172572.2), but the literature did not explore the performance of the microsphere as a filler material in polyvinyl chloride resin products.
[0006] Therefore, there is a demand for filler materials that can achieve high-level improvement in mechanical properties (such as toughness and strength), have excellent affinity with vinyl chloride resins, and produce products with good transparency. Summary of the Invention
[0007] <Problem to be solved by the invention>
[0008] In view of the above, the object of the present invention is to provide a vinyl chloride copolymer microsphere that can be widely used as a filler material for various resin products based on vinyl chloride resins, has excellent affinity with vinyl chloride resins, and can improve the mechanical properties of resin products to a high level (e.g., simultaneously improve strength and toughness) and suppress the decrease in transparency of resin products.
[0009] The purpose of this invention is to provide a method for manufacturing vinyl chloride copolymer microspheres, which can easily obtain the above-mentioned vinyl chloride copolymer microspheres at low cost, and furthermore, the obtained vinyl chloride copolymer microspheres also have high purity.
[0010] The present invention also aims to provide a resin composition comprising the above-mentioned vinyl chloride copolymer microspheres, a resin article made from the resin composition, and a method for manufacturing the resin article, wherein the resin article has excellent mechanical properties and transparency.
[0011] <Solutions for solving the problem>
[0012] According to the inventor's dedicated research, the above-mentioned technical problems can be solved by implementing the following technical solution:
[0013] [1]. A vinyl chloride copolymer microsphere comprising cross-linked vinyl chloride microspheres and graft portions grafted onto the surface of the cross-linked vinyl chloride microspheres.
[0014] The cross-linked vinyl chloride microspheres comprise unit A, which is based on a cross-linking agent, and unit B, which is based on vinyl chloride.
[0015] The graft portion comprises: a unit C based on a silane having a double bond and an alkoxy group and a unit D based on a (meth)acrylate.
[0016] [2]. According to the vinyl chloride copolymer microspheres of [1], wherein, relative to 100% by mass of all units constituting the crosslinked vinyl chloride microspheres, the proportion of unit A is 0.5% to 30% by mass, and the proportion of unit B is 70% to 99.5% by mass; and / or
[0017] The average particle size of the cross-linked vinyl chloride microspheres is less than 1200 nm; and / or
[0018] The gel content of the cross-linked vinyl chloride microspheres is not less than 30%.
[0019] [3]. According to [1] or [2], the proportion of the grafted portion is 15 to 120% by mass relative to 100% by mass of the total mass of the crosslinked vinyl chloride microspheres;
[0020] Relative to the total mass of all units constituting the graft portion, the proportion of unit C is 30-80% by mass, and the proportion of unit D is 20-70% by mass.
[0021] [4]. Vinyl chloride copolymer microspheres according to any one of [1] to [3], wherein the silane having double bonds and alkoxy groups comprises at least one selected from (meth)acryloyloxytrialkoxysilane and vinyltrialkoxysilane; and / or
[0022] The alkoxy group in the silane having a double bond and an alkoxy group is an alkoxy group with 1 to 6 carbon atoms.
[0023] [5]. A method for manufacturing vinyl chloride copolymer microspheres according to any one of [1] to [4], comprising: adding cross-linked vinyl chloride microspheres, a silane having double bonds and alkoxy groups, (meth)acrylate, an initiator and a solvent to a polymerization reactor to carry out a surface graft polymerization reaction, thereby grafting molecular chains comprising unit C based on silane having double bonds and alkoxy groups and unit D based on (meth)acrylate onto the surface of the cross-linked vinyl chloride microspheres.
[0024] [6]. According to the manufacturing method described in [5], wherein the temperature of the polymerization reaction is 40–100°C and the time of the polymerization reaction is 4–24 hours; and / or
[0025] The solvent contains less than 100 ppm of water; and / or
[0026] The solvent is at least one selected from carboxylic acid ester solvents or ketone solvents; and / or
[0027] Relative to 100% of the total mass of the cross-linked vinyl chloride microspheres, the amount of the silane having double bonds and alkoxy groups is 50-300% by mass, and the amount of the (meth)acrylate is 40-200% by mass.
[0028] [7]. The manufacturing method according to [5] or [6] further includes: polymerizing a monomer mixture containing vinyl chloride and a crosslinking agent in a dispersion medium under conditions of optional dynamic action without using a dispersing agent and a chain transfer agent to obtain crosslinked vinyl chloride microspheres, wherein the dispersion medium is capable of dissolving the monomer mixture but not of dissolving the crosslinked vinyl chloride microspheres.
[0029] [8]. A resin composition comprising a vinyl chloride resin and vinyl chloride copolymer microspheres according to any one of [1] to [4].
[0030] [9]. A resin article made using the resin composition according to [8].
[0031]
[10] . A method of manufacturing a resin article according to [9], comprising: molding a resin composition according to [8] into a preform and subjecting the preform to a hot water treatment.
[0032] <The Effects of the Invention>
[0033] In this invention, cross-linked vinyl chloride microspheres are used as the core of the vinyl chloride-based copolymer microspheres, and the core is grafted with units comprising silanes having double bonds and alkoxy groups and units based on (meth)acrylates. Therefore, when these vinyl chloride-based copolymer microspheres are used as filler materials for vinyl chloride-based resin products, they not only exhibit excellent compositional affinity with vinyl chloride-based resins, but also possess the potential to form a cross-linked network through the hydrolytic condensation of silane bonds as macromolecular cross-linking agents. Thus, the vinyl chloride-based copolymer microspheres of this invention exhibit high affinity for vinyl chloride-based resins, can significantly improve the mechanical properties of resin products, and can suppress the decrease in the transparency of resin products.
[0034] Furthermore, the manufacturing method of vinyl chloride-based copolymer microspheres is easy, and their structure and composition are easily adjustable, thus allowing for customization based on the raw material resin used in the resin product. Therefore, the vinyl chloride-based copolymer microspheres of the present invention can be widely used as filler materials for various resin products based on vinyl chloride-based resins.
[0035] Furthermore, the vinyl chloride copolymer microspheres of the present invention can be obtained by (self-stabilizing) precipitation polymerization, resulting in microspheres with high purity, which is more conducive to their effectiveness.
[0036] Based on the above, the present invention also provides a resin composition comprising the above-mentioned vinyl chloride copolymer microspheres, a resin article made from the resin composition, and a method for manufacturing the resin article, wherein the resin article has excellent mechanical properties and transparency.
[0037] Furthermore, by forming a resin composition comprising the above-mentioned vinyl chloride copolymer microspheres into a resin preform and exposing the preform to hot water to prepare a resin product, the mechanical properties and transparency of the resin product can be further improved. Attached Figure Description
[0038] Figure 1 The image shown is a SEM image of the cross-linked microspheres obtained in Synthesis Example 1 of the present invention.
[0039] Figure 2 The image shown is a SEM image of the vinyl chloride copolymer microspheres obtained in Manufacturing Example 1 of the present invention. Detailed Implementation
[0040] Various exemplary embodiments, features, and aspects of the present invention will be described in detail below. The term "exemplary" as used herein means "serving as an example, embodiment, or illustration." Any embodiment described herein as "exemplary" is not necessarily to be construed as superior to or better than other embodiments.
[0041] Furthermore, to better illustrate the present invention, numerous specific details are set forth in the following detailed embodiments. Those skilled in the art should understand that the present invention can be practiced without certain specific details. In other instances, methods, means, apparatus, and steps well known to those skilled in the art have not been described in detail in order to highlight the spirit of the present invention.
[0042] Unless otherwise stated, all units used in this specification are international standard units, and all numerical values and ranges appearing in this invention should be understood to include systematic errors that are unavoidable in industrial production.
[0043] In this specification, the word "may" has two meanings: to perform a certain process and not to perform a certain process.
[0044] In this specification, references to "some specific / preferred embodiments," "other specific / preferred embodiments," "implementation," etc., refer to specific elements (e.g., features, structures, properties, and / or characteristics) related to that embodiment, which are included in at least one of the embodiments described herein and may or may not be present in other embodiments. Furthermore, it should be understood that these elements may be combined in any suitable manner in various embodiments.
[0045] In this specification, the range of values referred to as "value A to value B" refers to the range including the endpoint values A and B.
[0046] Numerical ranges indicated by "above" and "below" refer to ranges that include endpoint values. Numerical ranges indicated by "greater than" and "less than" refer to ranges that do not include endpoint values.
[0047] Unless otherwise specified, "%" in this instruction manual refers to the percentage content by mass.
[0048] In this specification, "optional" or "optionally" means that the event or situation described below may or may not occur, and the description includes both the scenario in which the event occurs and the scenario in which the event does not occur.
[0049] In this specification, a “unit” in a polymer refers to a polymeric unit derived from a monomer formed by monomer polymerization, and a polymeric unit formed by processing the polymer to transform a portion of that polymeric unit into a different structure.
[0050] In this instruction manual, when "room temperature" or "room temperature" is used, the temperature can be between 10 and 30°C.
[0051] Unless otherwise specified, the term "particle size" used in this manual refers to "average particle size," which can be measured using third-party software such as ImageJ and electron scanning microscope images. The average particle size and its distribution can also be measured using a laser particle size analyzer.
[0052] <vinyl chloride-based copolymer microspheres>
[0053] The vinyl chloride copolymer microspheres of the present invention include cross-linked vinyl chloride microspheres and graft portions grafted onto the surface of the cross-linked vinyl chloride microspheres. The cross-linked vinyl chloride microspheres contain unit A based on a cross-linking agent and unit B based on vinyl chloride. The graft portions include unit C based on a silane having a double bond and an alkoxy group and unit D based on (meth)acrylate.
[0054] In this invention, the term "microsphere" refers to an object that is spherical or quasi-spherical in shape as a whole.
[0055] In this invention, the vinyl chloride-based copolymer microspheres have a core-shell structure. The shell portion is composed of grafted portions, and the core portion is composed of vinyl chloride-based copolymer microspheres.
[0056] In this invention, there is no particular limitation on the average particle size of the vinyl chloride copolymer microspheres, which can be appropriately adjusted according to actual needs. In some preferred embodiments, from the viewpoint of more easily obtaining vinyl chloride copolymer microspheres, the average particle size of the vinyl chloride copolymer microspheres is preferably less than 1200 nm, more preferably less than 1000 nm, and even more preferably less than 900 nm; in addition, it is usually 40 nm or more, for example 60 nm or more, 80 nm or more, or 100 nm or more.
[0057] The following will describe in detail the components of the vinyl chloride copolymer microspheres.
[0058] (Cross-linked vinyl chloride microspheres)
[0059] In this invention, the crosslinked vinyl chloride microspheres may contain unit A based on a crosslinking agent and unit B based on vinyl chloride.
[0060] There are no particular restrictions on the type of crosslinking agent; it can be selected appropriately according to actual needs. The crosslinking agent is a monomer with difunctionality or higher that can polymerize with vinyl chloride.
[0061] In some preferred embodiments, the crosslinking agent is preferably at least one selected from allyl esters and (meth)acrylates that are more than difunctional.
[0062] Examples of allyl esters with difunctionality or higher include, but are not limited to, diallyl phthalate and diallyl maleate. These monomers can be used alone or in combination of two or more.
[0063] Examples of (meth)acrylates with more than two functionalities include, but are not limited to, difunctional (meth)acrylates such as ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, propylene glycol dimethacrylate, dipropylene glycol dimethacrylate, tripropylene glycol dimethacrylate, polypropylene glycol dimethacrylate, butanediol dimethacrylate, pentanediol dimethacrylate, etc.; trifunctional (meth)acrylates such as pentaerythritol trimethacrylate, trihydroxymethane trimethacrylate, and glycerol trimethacrylate, etc.; tetrafunctional (meth)acrylates such as pentaerythritol tetramethacrylate; pentafunctional (meth)acrylates such as dipentaerythritol pentamethacrylate; and hexafunctional (meth)acrylates such as dipentaerythritol hexamethacrylate, etc. These monomers can be used alone or in combination of two or more.
[0064] In some more preferred embodiments, the crosslinking agent is more preferably at least one selected from difunctional allyl esters and difunctional (meth)acrylates.
[0065] Furthermore, without compromising the technical effects of the present invention, the cross-linked vinyl chloride microspheres may optionally contain other main chain units based on other main chain monomers for the purpose of adjusting the performance of the cross-linked vinyl chloride microspheres.
[0066] Examples of other main-chain monomers here include, but are not limited to, monofunctional styrene monomers, such as styrene, α-methylstyrene, o-methylstyrene, etc.; monofunctional (meth)acrylates, such as C1-13 alkyl (meth)acrylates, C1-13 hydroxyalkyl (meth)acrylates, glycidyl (meth)acrylates; monofunctional vinyl ester monomers, such as vinyl acetate, vinyl propionate, vinyl butyrate, allyl acetate, etc.; and monofunctional vinyl ether monomers, such as methyl vinyl ether, ethyl vinyl ether, propyl vinyl ether, butyl vinyl ether, pentyl vinyl ether, hexyl vinyl ether, etc. These monomers can be used alone or in combination of two or more.
[0067] In this invention, there are no particular restrictions on the proportion of each unit contained in the cross-linked vinyl chloride microspheres, which can be adjusted appropriately according to actual needs.
[0068] In some preferred embodiments, the proportion of unit A relative to all 100% mass of the units constituting the cross-linked vinyl chloride microspheres is preferably 0.5% to 30% by mass, more preferably 2% to 25% by mass, and even more preferably 4% to 20% by mass.
[0069] In some preferred embodiments, the proportion of unit B relative to all 100% mass of the units constituting the crosslinked vinyl chloride microspheres is preferably 70% to 99.5% by mass, more preferably 75% to 98% by mass, and even more preferably 80% to 96% by mass.
[0070] In some preferred embodiments, the proportion of other main chain units relative to 100% by mass of all units constituting the crosslinked vinyl chloride microspheres is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less.
[0071] In addition, the gel content is used in this invention to evaluate the degree of cross-linking of cross-linked vinyl chloride microspheres. The method for testing the gel content is as follows: a certain mass m0 of dried resin is accurately weighed and placed in a filter cartridge. Tetrahydrofuran is added to a Soxhlet extractor, and the filter cartridge is placed in the extraction chamber for more than 24 hours. After the insoluble matter is dried, it is weighed to obtain the mass m1. The ratio of the mass of insoluble matter to the mass of resin, i.e., (m1 / m0) × 100%, is the gel content.
[0072] In some preferred embodiments, to further improve the morphology and uniformity of the resulting functionalized microspheres and facilitate graft polymerization, the gel content of the crosslinked vinyl chloride-based microspheres is preferably not less than 30%, more preferably 40% or more, further preferably 50% or more, particularly preferably 65% or more, and especially preferably 80% or more. There is no particular limitation on the upper limit of the gel content, which can be 100%. Furthermore, from the viewpoint of better improving mechanical properties, the gel content is preferably 98% or less, more preferably 95% or less, and even more preferably 90% or less.
[0073] In this invention, the cross-linked vinyl chloride microspheres can be solid, hollow, or porous.
[0074] There is no particular limitation on the average particle size of the cross-linked vinyl chloride microspheres, as long as the vinyl chloride copolymer microspheres of the present invention can be obtained. In some preferred embodiments, the average particle size of the cross-linked vinyl chloride microspheres is preferably less than 1200 nm, more preferably less than 1000 nm, more preferably less than 900 nm, for example less than 800 nm, etc. There is no particular limitation on the lower limit of the average particle size of the cross-linked vinyl chloride microspheres, which can generally be 40 nm or more, for example 60 nm or more, 80 nm or more, or 100 nm or more.
[0075] (Grafting point)
[0076] In this invention, the graft portion is chemically grafted onto the surface of cross-linked vinyl chloride microspheres. This graft portion comprises a unit C based on a silane having double bonds and alkoxy groups, and a unit D based on (meth)acrylates.
[0077] There are no particular restrictions on the types of silanes with double bonds and alkoxy groups; they can be selected appropriately according to actual needs.
[0078] From the viewpoint of ensuring the performance of vinyl chloride-based copolymer microspheres, the alkoxy group of the silane having double bonds and alkoxy groups is preferably an alkoxy group with 1 to 6 carbon atoms, more preferably an alkoxy group with 1 to 3 carbon atoms. Furthermore, from the same viewpoint, the number of alkoxy groups in the silane having double bonds and alkoxy groups is preferably 2 or more, more preferably 3.
[0079] From the viewpoint that it is more advantageous to obtain vinyl chloride-based copolymer microspheres, the double bonds of silanes with double bonds and alkoxy groups can be derived from (meth)acryloyloxy, vinyl or allyl groups.
[0080] In some preferred embodiments, from the viewpoint of polymerization activity and raw material source cost, the silane having double bonds and alkoxy groups includes at least one selected from (meth)acryloyloxytrialkoxysilane and vinyltrialkoxysilane, more preferably including (meth)acryloyloxytrialkoxysilane.
[0081] In some more preferred embodiments, the silane having a double bond and an alkoxy group preferably includes at least one selected from (meth)acryloyloxytrimethoxysilane, (meth)acryloyloxytriethoxysilane, vinyltrimethoxysilane, and vinyltrimethoxysilane, and more preferably includes at least one selected from (meth)acryloyloxytrimethoxysilane or (meth)acryloyloxytriethoxysilane.
[0082] There are no particular restrictions on the types of (meth)acrylates; appropriate selection can be made according to actual needs. Examples of (meth)acrylates include, but are not limited to: alkyl (meth)acrylates, such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-pentyl (meth)acrylate, tert-pentyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-dodecyl (meth)acrylate, undecyl (meth)acrylate, isoundecyl (meth)acrylate, cyclohexyl (meth)acrylate, etc. The monomers include tert-butylcyclohexyl methacrylate, cyclooctyl methacrylate, etc.; glycidyl methacrylate; hydroxyalkyl methacrylates, such as hydroxyethyl methacrylate, hydroxypropyl methacrylate, 4-hydroxybutyl methacrylate, 2-hydroxyhexyl methacrylate, 6-hydroxyhexyl methacrylate, 8-hydroxyoctyl methacrylate, 10-hydroxydecyl methacrylate, etc.; alkoxyalkyl methacrylates, such as methoxyethyl methacrylate, ethoxyethyl methacrylate, methoxypropyl methacrylate, ethoxypropyl methacrylate; aminoalkyl methacrylates, such as dimethylaminomethyl methacrylate, dimethylaminoethyl methacrylate, dimethylaminopropyl methacrylate; isobornyl methacrylate, etc. These monomers can be used alone or in combination of two or more.
[0083] From the viewpoint of ensuring the performance of vinyl chloride copolymer microspheres, (meth)acrylate is preferably an alkyl methacrylate, more preferably at least one selected from (meth)acrylate, (meth)ethyl methacrylate, (meth)acrylate n-propyl methacrylate, (meth)acrylate isopropyl methacrylate, and (meth)acrylate n-butyl methacrylate, and even more preferably (meth)acrylate.
[0084] Furthermore, without compromising the technical effects of the present invention, cross-linked vinyl chloride microspheres may optionally contain other grafting units based on other grafting monomers for the purpose of adjusting the performance of the grafted portion.
[0085] Examples of other grafting monomers here include, but are not limited to, monofunctional styrene monomers, such as styrene, α-methylstyrene, o-methylstyrene, etc.; monofunctional vinyl ester monomers, such as vinyl acetate, vinyl propionate, vinyl butyrate, allyl acetate, etc.; and monofunctional vinyl ether monomers, such as methyl vinyl ether, ethyl vinyl ether, propyl vinyl ether, butyl vinyl ether, pentyl vinyl ether, hexyl vinyl ether, etc. These monomers can be used alone or in combination of two or more.
[0086] In this invention, there are no particular restrictions on the proportions of the units included in the grafting portion, which can be adjusted appropriately according to actual needs.
[0087] In some preferred embodiments, the proportion of unit C relative to all units 100% of the total mass constituting the graft portion is preferably 30-80% by mass, more preferably 40-70% by mass, and even more preferably 45-65% by mass.
[0088] In some preferred embodiments, the proportion of unit D relative to all units 100% of the total mass constituting the graft portion is preferably 20-70% by mass, more preferably 30-60% by mass, and even more preferably 35-55% by mass.
[0089] In some preferred embodiments, the proportion of other grafting units relative to all units constituting the graft portion by mass is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less.
[0090] In this invention, there are no particular restrictions on the ratio of the grafted portion to the cross-linked vinyl chloride microspheres, which can be adjusted appropriately according to actual needs.
[0091] Preferably, from the viewpoint of better demonstrating the role of the graft and better maintaining the morphology of the cross-linked vinyl chloride microspheres, the proportion of the graft (i.e., the grafting rate) relative to 100% of the total mass of the cross-linked vinyl chloride microspheres is preferably 15 to 120% by mass, more preferably 30 to 100% by mass.
[0092] In this invention, there are no particular limitations on the preparation method of vinyl chloride-based copolymer microspheres, and various means known in the art can be used. Preferably, the vinyl chloride-based copolymer microspheres of this invention are obtained by the method described in the "Method for Manufacturing Vinyl Chloride-Based Copolymer Microspheres" section below.
[0093] <Manufacturing Method of Vinyl Chloride Copolymer Microspheres>
[0094] The method for manufacturing vinyl chloride copolymer microspheres of the present invention includes: adding cross-linked vinyl chloride microspheres, silanes having double bonds and alkoxy groups, (meth)acrylates, an initiator, and a solvent into a polymerization reactor to carry out a surface grafting polymerization reaction, thereby grafting molecular chains comprising unit C based on silanes having double bonds and alkoxy groups and unit D based on (meth)acrylates onto the surface of the cross-linked vinyl chloride microspheres.
[0095] Without compromising the technical effects of the present invention, other grafting monomers may optionally be used in addition to silanes and (meth)acrylates having double bonds and alkoxy groups as grafting monomers for the purpose of adjusting the performance of the grafted portion.
[0096] The graft polymerization reaction is achieved by the following: the residual double bonds on the surface of the cross-linked vinyl chloride microspheres are copolymerized with free radicals between silanes and (meth)acrylates having double bonds and alkoxy groups, thereby covalently connecting the grafted parts to the cross-linked vinyl chloride microspheres.
[0097] Details of the cross-linked vinyl chloride microspheres, silanes with double bonds and alkoxy groups, (meth)acrylates and other grafted monomers are as described above and will not be repeated here.
[0098] In addition, there are no particular restrictions on the preparation method of cross-linked vinyl chloride microspheres. They can usually be prepared by suspension polymerization, emulsion polymerization, interfacial polymerization, precipitation polymerization, etc.
[0099] In some preferred embodiments, the cross-linked polyvinyl chloride microspheres are obtained by precipitation polymerization, which makes the surface of the microspheres cleaner and facilitates graft polymerization.
[0100] In some preferred embodiments, without the use of dispersants and chain transfer agents, a monomer mixture containing vinyl chloride and a crosslinking agent is polymerized in a dispersion medium under optionally applied dynamic conditions to obtain crosslinked vinyl chloride microspheres. The dispersion medium is capable of dissolving the monomer mixture but not the crosslinked vinyl chloride microspheres.
[0101] More specifically, the preparation of these microspheres can refer to the preparation technology of cross-linked polyvinyl chloride nanoparticles described in Chinese publication CN115975097A. The cross-linked polyvinyl chloride microspheres of different particle sizes can be controlled by adjusting the polymerization conditions, which will not be elaborated here.
[0102] In this invention, there are no particular restrictions on the amount of cross-linked vinyl chloride microspheres, silanes with double bonds and alkoxy groups, (meth)acrylates, and other grafted monomers, as long as the desired vinyl chloride copolymer microspheres can be obtained.
[0103] In some preferred embodiments, the amount of silane having double bonds and alkoxy groups is preferably 50 to 300% by mass, more preferably 55 to 250% by mass, and even more preferably 60 to 200% by mass, relative to 100% by mass of the total mass of the cross-linked vinyl chloride microspheres.
[0104] In some preferred embodiments, the amount of (meth)acrylate is preferably 40 to 200% by mass relative to 100% by mass of the total mass of the cross-linked vinyl chloride microspheres, more preferably 45 to 180% by mass, and even more preferably 50 to 150% by mass.
[0105] In some preferred embodiments, the amount of other grafted monomers is preferably 30% by mass or less, more preferably 20% by mass or less, and even more preferably 10% by mass or less, relative to 100% by mass of the total mass of the cross-linked vinyl chloride microspheres.
[0106] There are no particular restrictions on the type of initiator, as long as it can initiate graft polymerization. Preferably, the initiator is at least one selected from azo initiators or organic peroxide initiators.
[0107] Examples of azo initiators include, but are not limited to, azobisisobutyronitrile (AIBN) and azobisisoheptanenitrile (AIHH).
[0108] Examples of organic peroxide initiators include, but are not limited to, tert-butyl peroxyneoheptanoate, tert-butyl peroxyneodecanate, disec-butyl peroxydicarbonate, di(hexadecyl)dicarbonate peroxide, tert-pentyl peroxyneodecanate, tert-butyl peroxyneodecanate, di-(4-tert-butylcyclohexyl peroxydicarbonate), dicyclohexyl peroxydicarbonate, diisopropyl peroxydicarbonate, dibutyl peroxydicarbonate, di(2-ethylhexyl peroxydicarbonate), tert-butyl peroxydiethylhexanoate, ditetradecyl peroxydicarbonate, tert-butyl peroxyacetate, isopropylphenyl peroxyneodecanate, ditert-butyl peroxydicarbonate, cyclohexylsulfonyl acetyl peroxydioxide, diisobutyryl peroxydioxide, 1,1,3,3-tetramethylbutyl peroxyneodecanate, di-3-methoxybutyl peroxydicarbonate, and 1,1,3,3-tetramethylbutyl peroxydicarbonate.
[0109] The amount of initiator relative to the total amount of all grafted monomers (100% by mass) can be, for example, 0.1% to 4% by mass, more preferably 0.5% to 3% by mass.
[0110] There are no particular restrictions on the type of solvent, as long as it is a good solvent for all grafted monomers and their polymers. This is because the solvent provides the solvent environment required for the grafting reaction and dissolves byproducts such as polymers of the grafted monomers and unreacted monomers that may be generated during the grafting reaction, which is beneficial for obtaining purer functionalized microspheres in post-processing.
[0111] Examples of solvents include, but are not limited to: alkane solvents, such as n-hexane, n-heptane, cyclohexane, pentane, n-octane, etc.; haloalkane solvents, such as chloromethane, dichloromethane, chloroform, etc.; carboxylic acid ester solvents, such as ethyl acetate, butyl acetate, ethyl butyrate, isoamyl acetate, etc.; ether solvents, such as diethyl ether, butyl ether, tetrahydrofuran, etc.; amide solvents, such as N,N-dimethylformamide, N,N-diethylformamide, etc.; ketone solvents, such as acetone, butanone, and cyclohexanone, etc.; and aromatic hydrocarbon solvents, such as benzene, toluene, etc. These solvents can be used alone or in combination of two or more.
[0112] In some preferred embodiments, the solvent preferably comprises at least one selected from carboxylic acid ester solvents and ketone solvents.
[0113] In some preferred embodiments, the solvent is an organic solvent that has been dehydrated, because alkoxysilanes are prone to moisture-curing crosslinking reactions in humid environments.
[0114] There are no particular restrictions on the methods for solvent drying. Physical dehydration techniques well known in the art, such as molecular sieve adsorption, desiccant dehydration, azeotropic distillation, and freeze dehydration, as well as chemical dehydration techniques such as metal reflux dehydration and reactive reagents, can all be used to treat the above-mentioned solvents.
[0115] In some more preferred embodiments, the water content in the solvent is preferably less than 100 ppm, more preferably less than 80 ppm, further preferably less than 50 ppm, and especially preferably less than 40 ppm.
[0116] In addition, preferably, in the graft polymerization reaction system of the present invention, the total mass concentration of cross-linked polyvinyl chloride microspheres and all graft monomers is preferably 5-20%, more preferably 7-15%.
[0117] There are no particular restrictions on the conditions for the graft polymerization reaction; they can be adjusted appropriately according to actual needs.
[0118] In some specific implementations, the temperature of the graft polymerization reaction can be 40–100°C, for example 50–90°C, for example 60–85°C.
[0119] In some specific implementations, the graft polymerization reaction can take 4 to 24 hours, for example 5 to 20 hours, or for example 6 to 15 hours.
[0120] The graft polymerization reaction of the present invention can optionally be carried out under dynamic conditions (e.g., stirring, ultrasound, oscillation, and other dynamic conditions conventional in the art).
[0121] Furthermore, the atmosphere for the graft polymerization reaction of the present invention can be an air atmosphere, air with adjusted oxygen partial pressure, or an inert gas atmosphere such as nitrogen or argon. From the viewpoint of being more favorable to the graft polymerization reaction, an inert gas atmosphere is preferred.
[0122] In addition, the preparation method of the present invention also includes other steps conventional in the art, such as separating cross-linked vinyl chloride microspheres or vinyl chloride copolymer microspheres from the polymerization system by means of centrifugation, ultrafiltration, etc., washing the vinyl chloride microspheres or vinyl chloride copolymer microspheres, drying the vinyl chloride microspheres or vinyl chloride copolymer microspheres, and recovering various monomers remaining in the reaction system after the reaction is completed.
[0123] <Resin Composition>
[0124] The resin composition of the present invention comprises a vinyl chloride-based resin and the above-mentioned vinyl chloride copolymer microspheres of the present invention.
[0125] There is no particular limitation on the content of the above-mentioned vinyl chloride copolymer microspheres in the resin composition, and it can be adjusted appropriately according to actual needs. For example, relative to 100% of the total mass of the vinyl chloride resin, the content of the vinyl chloride copolymer microspheres can be 0.1 to 50% by mass, more preferably 0.5 to 30% by mass, even more preferably 0.8 to 20% by mass, and particularly preferably 1 to 15% by mass.
[0126] In this invention, the vinyl chloride-based resin can be a vinyl chloride homopolymer (PVC) or a vinyl chloride copolymer. Preferably, the vinyl chloride copolymer is used where the vinyl chloride-based unit in the copolymer accounts for 40% or more by mass.
[0127] In addition to vinyl chloride-based resins, the compositions of the present invention may also contain other components, examples of which include: other resins, such as propylene resins, ethylene resins, polyester resins such as polyethylene terephthalate, styrene resins, fluororesins, silicone resins, polyamide resins, polyimide resins, etc.; rubbers, such as styrene-butadiene rubber, nitrile rubber, butyl rubber, chloroprene rubber, isoprene rubber, cis-butadiene rubber, ethylene propylene rubber, ethylene propylene diene rubber, silicone rubber; thermoplastic elastomers, such as olefin-based thermoplastic elastomers, styrene-based thermoplastic elastomers, polyamide-based thermoplastic elastomers, polyester-based thermoplastic elastomers, polyvinyl chloride-based thermoplastic elastomers, polyurethane-based thermoplastic elastomers, fluoropolymer-based thermoplastic elastomers, etc. These can be used alone or in combination of two or more.
[0128] Furthermore, the resin composition of the present invention may optionally include, in any amount, various additives commonly known in the art, such as fillers, pigments, plasticizers, ultraviolet absorbers, light stabilizers, matting agents, surfactants, leveling agents, surface conditioners, degassing agents, heat stabilizers, antistatic agents, rust inhibitors, silane coupling agents, antifouling agents, antibacterial agents, foaming agents, lubricants, and other crosslinking agents. These can be used alone or in combination of two or more.
[0129] The resin compositions of the present invention can be prepared by methods commonly known in the art. For example, all components constituting the resin compositions of the present invention can be mixed using standard mixing equipment such as conventional mixers, Banbury or Brabender mixers, extruders, kneaders, and two-roll mills. There are no particular limitations on the method of composition preparation; the above mixing can be carried out in a single-stage or multi-stage manner depending on the desired composition. There are also no particular limitations on the mixing temperature and mixing speed; they can be appropriately selected according to the desired composition.
[0130] <Resin Products>
[0131] The resin articles of the present invention are made using the resin composition described above. That is, the resin articles of the present invention are molded articles made from the resin composition described above.
[0132] In this invention, there are no particular limitations on the manufacturing method of the resin article, and it can be made by methods generally known in the art. For example, the resin composition of the present invention can be molded (preferably, melt-molded) into a preform, and then the preform can be post-processed to produce a specific molded article.
[0133] In some preferred embodiments, the resin articles of the present invention are preferably molded articles formed by melt molding, that is, molded articles formed by melt molding.
[0134] There are no particular limitations on the method for melting and molding the resin composition of the present invention. Methods commonly known in the art can be used, such as extrusion molding, injection molding, blow molding, die (pressure) molding, calendering, etc.
[0135] There are no particular restrictions on the post-processing methods. In some preferred embodiments, the methods used in the section on "Manufacturing Methods of Resin Articles" below may be employed to further improve mechanical properties.
[0136] In this invention, resin products can be formed into products independently, or they can be formed into products by combining with accessories made of other materials (such as ceramic accessories, metal accessories, and other resin products).
[0137] Furthermore, when used in conjunction with accessories made of other materials, post-processing may be performed either before or after the aforementioned combination.
[0138] <Manufacturing Methods of Resin Products>
[0139] The method for manufacturing the resin article of the present invention includes molding the resin composition of the present invention into a preform and subjecting the preform to hot water treatment.
[0140] As described above, the molding of the resin composition of the present invention is preferably the melt molding of the resin composition of the present invention.
[0141] Hot water treatment can be carried out by immersing at least a portion of the precast component in hot water or by spraying hot water onto at least a portion of the precast component.
[0142] There are no particular restrictions on the conditions for hot water treatment, which can be appropriately adjusted according to the actual needs such as the implementation method of hot water treatment and the size and shape of the part to be treated.
[0143] In some specific implementations, the temperature for hot water treatment can be, for example, 40–100°C, or, for example, 45–95°C.
[0144] In some specific implementations, the hot water treatment time can be, for example, 30 seconds to 10 hours, or 1 minute to 8 hours.
[0145] Example
[0146] The embodiments of the present invention will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer are followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0147] (Gel content of cross-linked vinyl chloride microspheres)
[0148] The method for testing gel content is as follows: Accurately weigh a certain mass m0 of dried cross-linked vinyl chloride microspheres and place them in a filter cartridge. Add tetrahydrofuran to a Soxhlet extractor and place the filter cartridge in the extraction chamber for more than 24 hours. After the insoluble matter is dried, weigh it to obtain the mass m1. The ratio of the mass of the insoluble matter to the original mass of the cross-linked vinyl chloride microspheres, i.e. (m1 / m0) × 100%, is the gel content.
[0149] (Proportion of the grafted portion)
[0150] The proportion of grafted parts (grafting rate) is determined according to formula n. (接枝率) %=(m 接枝后 -m 接枝前 ) / m 接枝前 Calculated by multiplying by 100%. Where m... 接枝前 m represents the mass of the cross-linked vinyl chloride microspheres before grafting. 接枝后 The quality of the grafted cross-linked vinyl chloride microsphere system.
[0151] (Composition ratio of grafting portion)
[0152] The mixture after the graft polymerization reaction is taken out of the reactor and centrifuged to obtain a supernatant and a solid. The supernatant contains unreacted monomers and sometimes byproducts. The content of each monomer in the supernatant is determined by gas chromatography. When byproducts are present, the weight of the extracted byproducts is weighed and the composition of the byproducts is determined by mass spectrometry. The composition ratio of the grafted part can be obtained by subtracting the content of each monomer in the supernatant from the amount of each component fed in the initial feed.
[0153] (particle size)
[0154] The microstructure of each synthesized microsphere was characterized using scanning electron microscopy (SEM). The particle size of 100 microspheres was measured and calculated according to the following formula:
[0155]
[0156] Among them, D n Indicates number-average particle size. (Using D) n As the average particle size.
[0157] (Mechanical properties)
[0158] Vinyl chloride copolymer microspheres were added to polyvinyl chloride matrix through blending, and then mixed using a two-roll mill. The mixture was then hot-pressed at 180°C for 5 minutes and cold-pressed for 5 minutes to obtain a sample. In an embodiment involving hot water treatment, the sample was also treated with hot water before testing.
[0159] The prepared sample was cut into dumbbell-shaped strips, and its tensile strength was determined according to GB / T1040-2006. In this invention, tensile strength is used to evaluate the strength of the sample.
[0160] The prepared sample was cut into strips with a length of 80±2 mm, a width of 10.0±0.2 mm, and a thickness of 4.0±0.2 mm. The impact strength was then determined according to GB / T1043.1-2008. In this invention, impact strength is used to evaluate the toughness of the sample.
[0161] (Transparency)
[0162] The light transmittance in the wavelength range of 400–800 nm was measured using a UV-Vis spectrophotometer. In this invention, a light transmittance below 70% is defined as poor, a light transmittance greater than 70% but below 80% is defined as good, and a light transmittance greater than 80% is defined as excellent. In this invention, "good" and "excellent" are acceptable, while "poor" is unacceptable.
[0163] <Synthesis example 1>
[0164] 3.6 g of crosslinking agent DAM (dallyl maleate), 1.46 g of initiator di-(4-tert-butylcyclohexyl peroxide), and 252 g of a mixed solvent of hexane and ethanol (V:V=93:7) were added to a 500 ml reactor. After evacuation, 45 g of vinyl chloride (VCM) was added. The reaction was carried out at 45 °C and a stirring speed of 400 r / min for 30 h. Crosslinked vinyl chloride microspheres were then obtained. The obtained microspheres were centrifuged, washed, and dried in a vacuum oven at 45 °C to obtain pure crosslinked vinyl chloride microspheres Q1.
[0165] <Synthesis example 2>
[0166] Except for reducing the amount of crosslinking agent DAM from 3.6 g to 1.8 g, crosslinked vinyl chloride microspheres Q2 were obtained in the same manner as in Synthesis Example 1.
[0167] <Synthesis example 3>
[0168] Except that the amount of crosslinking agent DAM was increased from 3.6 g to 7.2 g, crosslinked vinyl chloride microspheres Q3 were obtained in the same manner as in Synthesis Example 1.
[0169] Details of the cross-linked vinyl chloride microspheres obtained in Synthetic Examples 1 to 3 are shown in Table 1 below.
[0170] Table 1
[0171]
[0172] <Manufacturing Example 1>
[0173] 13g of microspheres Q1, 4.5g of γ-methacryloyloxypropyltrimethoxysilane (KH570), 3g of methyl methacrylate (MMA), and 20g of ethyl acetate (Q1:KH570:MMA mass ratio of 1:1.5:1) were added to a 100ml round-bottom flask. Azobisisobutyronitrile (AIBN) initiator and a stir bar were added. The flask was purged with nitrogen for 10min. The round-bottom flask was then placed in a constant-temperature oil bath and stirred at 75℃ for 8h. After the reaction was completed, the flask was washed several times with ethyl acetate and n-hexane. The washed solid was dried in a vacuum oven at 45℃ to obtain vinyl chloride copolymer microspheres S1 with grafted parts.
[0174] <Manufacturing Example 2>
[0175] Except for replacing the feed mass ratio of Q1:KH570:MMA from 1:1.5:1 to 1:1:1.5, vinyl chloride copolymer microspheres S2 with grafted portions were obtained in the same manner as in Manufacturing Example 1.
[0176] <Manufacturing Example 3>
[0177] Except for replacing the feed mass ratio of Q1:KH570:MMA from 1:1.5:1 to 1:2:1, vinyl chloride copolymer microspheres S3 with grafted portions were obtained in the same manner as in Manufacturing Example 1.
[0178] <Manufacturing Example 4>
[0179] Except for replacing the feed mass ratio of Q1:KH570:MMA from 1:1.5:1 to 1:4.2:2.8, vinyl chloride copolymer microspheres S4 with grafted portions were obtained in the same manner as in Manufacturing Example 1.
[0180] <Manufacturing Example 5>
[0181] Except for replacing the feed mass ratio of Q1:KH570:MMA from 1:1.5:1 to 1:3:2, vinyl chloride copolymer microspheres S5 with grafted portions were obtained in the same manner as in Manufacturing Example 1.
[0182] <Manufacturing Example 6>
[0183] Except for replacing the feed mass ratio of Q1:KH570:MMA from 1:1.5:1 to 1:0.75:0.5, vinyl chloride copolymer microspheres S6 with grafted portions were obtained in the same manner as in Manufacturing Example 1.
[0184] <Manufacturing Example 7>
[0185] Except for replacing the feed mass ratio of Q1:KH570:MMA from 1:1.5:1 to 1:0.45:0.3, vinyl chloride copolymer microspheres S7 with grafted portions were obtained in the same manner as in Manufacturing Example 1.
[0186] <Manufacturing Example 8>
[0187] Except for replacing microsphere Q1 with microsphere Q2, vinyl chloride copolymer microspheres S8 with grafted portions were obtained in the same manner as in Manufacturing Example 1.
[0188] <Manufacturing Example 9>
[0189] Except for replacing microsphere Q1 with microsphere Q3, vinyl chloride copolymer microspheres S9 with grafted portions were obtained in the same manner as in Manufacturing Example 1.
[0190] <Comparative Manufacturing Examples>
[0191] Except that MMA is not used, vinyl chloride copolymer microspheres CS with grafted portions are obtained in the same manner as in manufacturing example 1.
[0192] Details of the various vinyl chloride copolymer microspheres are shown in Table 2 below.
[0193] Table 2
[0194]
[0195] As can be seen from Table 2, under the same monomer dosage, the proportion of grafted parts in the comparative manufacturing example is lower than that in manufacturing example 1. This is because graft polymerization is difficult to carry out in the comparative manufacturing example when MMA is not used.
[0196] In addition, the inventors found during the experiments that, without using MMA, even increasing the ratio of KH570 to cross-linked microspheres did not effectively increase the proportion of grafted parts.
[0197] <Example 1>
[0198] Microspheres S1 (3 phr), heat stabilizer (SS-181) (2 phr), polyvinyl chloride (PVC, S-1000) (100 phr), and plasticizer (DOP) (10 phr) were plasticized on a two-roll mill at 160°C and 25 rpm for 10 min. Then, the mixture was hot-pressed at 180°C and 10 MPa for 5 min and cold-pressed for 5 min to obtain sample A1.
[0199] <Examples 2-9>
[0200] Except for replacing microsphere S1 with microspheres S2 to S9 respectively, samples A2 to A9 were obtained using the same method as in Example 1.
[0201] <Comparative Example 1>
[0202] Except for replacing microspheres S1 with microspheres Q1, sample CA1 was obtained using the same method as in Example 1.
[0203] <Comparative Example 2>
[0204] Except for replacing microspheres S1 with microspheres CS, sample CA2 was obtained using the same method as in Example 1.
[0205] <Example 10>
[0206] The sample A1 obtained in Example 1 was immersed in hot water at 80°C for 120 minutes to obtain sample B1 after hot water treatment.
[0207] It should be noted that, in the case of mechanical testing, the sample E1 subjected to hot water treatment can be a sample cut into the shape of a test strip.
[0208] <Examples 11-16>
[0209] Except for replacing sample A1 with samples A2 to A9 respectively, samples B2 to B9 were obtained using the same method as in Example 1.
[0210] <Comparative Example 3>
[0211] Except for replacing sample A1 with sample CA2, sample CB is obtained in the same way as in Example 1.
[0212] <Reference Example>
[0213] 2 phr of heat stabilizer (S-181), 100 phr of polyvinyl chloride (PVC), and 10 phr of plasticizer (DOP) were plasticized on a two-roll mill at 160°C and 25 rpm for 10 min, and then hot-pressed at 180°C and 10 MPa for 5 min and cold-pressed for 5 min to obtain reference sample C.
[0214] The test results for each sample are shown in Tables 3 and 4 below.
[0215] Table 3
[0216]
[0217] Table 4
[0218]
[0219] As can be seen from Tables 3 and 4, compared with Comparative Examples 1-2 and the Reference Example, Examples 1-16 of the present invention achieved improvements in tensile strength and impact strength while ensuring transparency. In particular, after hot water treatment, Examples 10-16 maintained acceptable transparency compared with Examples 1-9, while achieving further improvements in tensile strength and impact strength. However, Comparative Example 3 became unacceptable in terms of transparency compared with Comparative Example 2.
[0220] It should be noted that although the technical solution of the present invention has been described with specific examples, those skilled in the art will understand that the present invention should not be limited thereto.
[0221] The various embodiments of the present invention have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments. The terminology used herein is chosen to best explain the principles, practical application, or technical improvements to the embodiments in the market, or to enable others skilled in the art to understand the embodiments disclosed herein.
Claims
1. A vinyl chloride-based copolymer microsphere, characterized in that, It includes cross-linked vinyl chloride microspheres and graft portions grafted onto the surface of the cross-linked vinyl chloride microspheres. The cross-linked vinyl chloride microspheres comprise unit A, which is based on a cross-linking agent, and unit B, which is based on vinyl chloride. The graft portion comprises: a unit C based on a silane having a double bond and an alkoxy group and a unit D based on a (meth)acrylate.
2. The vinyl chloride-based copolymer microspheres according to claim 1, characterized in that, Relative to 100% mass of all units constituting the cross-linked vinyl chloride microspheres, the proportion of unit A is 0.5% to 30% by mass, and the proportion of unit B is 70% to 99.5% by mass; and / or The average particle size of the cross-linked vinyl chloride microspheres is less than 1200 nm; and / or The gel content of the cross-linked vinyl chloride microspheres is not less than 30%.
3. The vinyl chloride-based copolymer microspheres according to claim 1 or 2, characterized in that, The grafted portion accounts for 15-120% of the total mass of the cross-linked vinyl chloride microspheres. Relative to the total mass of all units constituting the graft portion, the proportion of unit C is 30-80% by mass, and the proportion of unit D is 20-70% by mass.
4. The vinyl chloride copolymer microspheres according to any one of claims 1 to 3, characterized in that, The silane having a double bond and an alkoxy group includes at least one selected from (meth)acryloyloxytrialkoxysilane and vinyltrialkoxysilane; and / or The alkoxy group in the silane having a double bond and an alkoxy group is an alkoxy group with 1 to 6 carbon atoms.
5. A method for manufacturing vinyl chloride copolymer microspheres according to any one of claims 1 to 4, characterized in that, include: Crosslinked vinyl chloride microspheres, silanes with double bonds and alkoxy groups, (meth)acrylates, initiators, and solvents are added to a polymerization reactor to carry out a surface grafting polymerization reaction, thereby grafting molecular chains comprising unit C based on silanes with double bonds and alkoxy groups and unit D based on (meth)acrylates onto the surface of the crosslinked vinyl chloride microspheres.
6. The manufacturing method according to claim 5, characterized in that, The polymerization reaction is carried out at a temperature of 40–100°C for a duration of 4–24 hours; and / or The solvent contains less than 100 ppm of water; and / or The solvent is at least one selected from carboxylic acid ester solvents or ketone solvents; and / or Relative to 100% of the total mass of the cross-linked vinyl chloride microspheres, the amount of the silane having double bonds and alkoxy groups is 50-300% by mass, and the amount of the (meth)acrylate is 40-200% by mass.
7. The manufacturing method according to claim 5 or 6, characterized in that, Also includes: Without using dispersants and chain transfer agents, and under optionally applied dynamic conditions, a monomer mixture containing vinyl chloride and a crosslinking agent is polymerized in a dispersion medium to obtain crosslinked vinyl chloride microspheres, wherein the dispersion medium is capable of dissolving the monomer mixture but not the crosslinked vinyl chloride microspheres.
8. A resin composition, characterized in that, It includes vinyl chloride-based resins and vinyl chloride-based copolymer microspheres according to any one of claims 1 to 4.
9. A resin product, characterized in that, It is made using the resin composition according to claim 8.
10. A method for manufacturing a resin article according to claim 9, characterized in that, include: The resin composition according to claim 8 is molded into a preform, and the preform is subjected to hot water treatment.
Citation Information
Patent Citations
Crosslinked vinyl chloride-based resin particles and method for preparing same
CN115975097A